If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 3 = -92 Reorder the terms: 3 + 5p = -92 Solving 3 + 5p = -92 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5p = -92 + -3 Combine like terms: 3 + -3 = 0 0 + 5p = -92 + -3 5p = -92 + -3 Combine like terms: -92 + -3 = -95 5p = -95 Divide each side by '5'. p = -19 Simplifying p = -19
| 7(a+5)-12=3a+6 | | 7(3x+1)=5x-8x | | 11(t-6)+4t=5(3t+2)-9 | | -16x^5-44x^4+30x^3=0 | | -3=x/6-6 | | 9x-(8x+2)=2x-40 | | 12-6x=3x-3 | | 6m+3(2m+5)+7=0 | | 6=n-8 | | -2AH=V^2-U^2 | | 28+3p=-4p | | x-2y^2-8y=3 | | 19x-4=10x-40 | | x-3/3=41/2 | | 4x-5x+x-7+2x= | | 4-3Y=30 | | 7x+8-x=35 | | 20=-12+u | | -1=r/4-2 | | -3z-7z+4=0 | | 2n^4+16n^2+21=x | | 63w-44-47w=-140 | | x-8y-2y=3 | | 0.20x=46 | | (2x+3)/5=9 | | 1-9x=0 | | (5y+5)-(2+4y)=9 | | 6x+7(2x-17)=41 | | 3(4x+6)=-35+41 | | 3x-2/5=x-2 | | b/9+1/4=11 | | 2x-6x-65=63 |